2021
DOI: 10.1016/j.isci.2021.102788
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelet and graphene oxide functionalization of face mask materials inhibits infectivity of trapped SARS-CoV-2

Abstract: Recent advancements in bidimensional nanoparticles production such as Graphene (G) and Graphene oxide (GO) have the potential to meet the need for highly functional personal protective equipment (PPE) against SARS-CoV-2 infection. The ability of G and GO to interact with microorganisms provides an opportunity to develop engineered textiles for use in PPE and limit the spread of COVID-19. PPE in current use in high-risk settings for COVID transmission provide only a physical barrier that decreases infection lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 49 publications
1
67
0
Order By: Relevance
“… 73 Maio et al showed that G/GO-functionalized polyurethane or cotton can reduce the viral load of SARS-CoV-2 by nearly 97 to 99%. 90 These NPs-based virus trapping methods can also apply to water filtration, air purification technology, etc.…”
Section: Combat Of Sars-cov-2mentioning
confidence: 99%
“… 73 Maio et al showed that G/GO-functionalized polyurethane or cotton can reduce the viral load of SARS-CoV-2 by nearly 97 to 99%. 90 These NPs-based virus trapping methods can also apply to water filtration, air purification technology, etc.…”
Section: Combat Of Sars-cov-2mentioning
confidence: 99%
“…Both G and GO show excellent antiviral activities against SARS-CoV-2. 71 After 30 minutes of contact, Das Jana et al found that copper oxide (Cu 2 O) NPs in a composite with G sheets inhibited the influenza A virus. 72 Cu 2 O/G disrupts the structural integrity of the viral envelope and the hemoagglutinin protein to impact the ability of the virus particles to enter the host cells and consequently prevents viral replication and infection.…”
Section: Nanostructured Antiviral Coatingsmentioning
confidence: 99%
“…Furthermore, graphene face masks minimize the use of non-biodegradable materials, thereby ensuring a clean and pollution-free environment. The free electrons of graphene nanoparticles are used to trap positively charged bacteria and viruses in face masks (De Maio et al, 2021;Seifi & Reza Kamali, 2021). Their high electrical conductivity and the flow of electrons from graphene-based materials cause oxidative stress in bacteria and viruses.…”
Section: Recent Advances In Graphene-based Face Masks and Benefitsmentioning
confidence: 99%